Evaluation of the efficacy of cisplatin–etoposide and the role of thoracic radiotherapy and prophylactic cranial irradiation in LCNEC. Issue 1 (29th March 2017) - Prelaj, Arsela; Rebuzzi, Sara Elena; Del Bene, Gabriella; Giròn Berrìos, Julio Rodrigo; Emiliani, Alessandra; De Filippis, Lucilla; Prete, Alessandra Anna; Pecorari, Silvia; Manna, Gaia; Ferrara, Carla; Rossini, Daniele; Longo, Flavia
In small-cell lung cancer (SCLC), the role of chemotherapy and radiotherapy is well established. Large-cell neuroendocrine carcinoma (LCNEC) shares several clinicopathological features with SCLC, but its optimal therapy is not defined. We evaluated clinical response and survival outcomes of advanced LCNEC treated in first-line therapy compared with SCLC. 72 patients with stage III–IV LCNEC (n=28) and extensive-stage SCLC (ES-SCLC) (n=44) received cisplatin–etoposide with/without thoracic radiotherapy (TRT) and prophylactic cranial irradiation (PCI). Comparing LCNEC with SCLC, we observed similar response rates (64.2% versus 59.1%), disease control rates (82.1% versus 88.6%), progression-free survival (mPFS) (7.4 versus 6.1 months) and overall survival (mOS) (10.4 versus 10.9 months). TRT and PCI in both histologies showed a benefit in mOS (34 versus 7.8 months and 34 versus 8.6 months, both p=0.0001). LCNEC patients receiving TRT showed an improvement in mPFS and mOS (12.5 versus 5 months, p=0.02 and 28.3 versus 5 months, p=0.004), similarly to ES-SCLC. PCI in LCNEC showed an increase in mPFS (20.5 versus 6.4 months, p=0.09) and mOS (33.4 versus 8.6 months, p=0.05), as in ES-SCLC. Advanced LCNEC treated with SCLC first-line therapy has a similar clinical response and survival outcomes to ES-SCLC. Cisplatin–etoposide is an efficient treatment for large-cell neuroendocrine carcinoma. RT and PCI improve survival. http://ow.ly/sBJo309HG8s